Empowering Community Protection Units (SATLINMAS) for Ensuring Security, Peace, and Order - Bhaskara, Gasti Dias; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2023)
This descriptive qualitative study investigates the empowerment of the Community Protection Unit (SATLINMAS) in fostering security, peace, and order in Sidoarjo Regency. Employing purposive sampling, data collection includes interviews, observation, and documentation. Analysis involves data collection, reduction, study, and conclusion drawing. The findings reveal suboptimal empowerment of SATLINMAS, as evidenced by the absence of key indicators. This study underscores the need for enhanced empowerment strategies to strengthen SATLINMAS' role in creating a secure and peaceful environment in Sidoarjo Regency. Highlight : The study assesses the effectiveness of SATLINMAS empowerment in fostering security and peace in Sidoarjo Regency. Data collection involves interviews, observation, and documentation, utilizing purposive sampling for information determination. Findings reveal suboptimal SATLINMAS empowerment, emphasizing the need for enhanced strategies to strengthen its role in maintaining a secure and peaceful environment Keywords: SATLINMAS, Empowerment, Security, Peace, Sidoarjo Regency